Empowering Sharia MSMEs for Inclusive Economic Growth: A Study of the Role of Sharia Financing for MSMEs in East Java Province - Yolanda, Orchidea Widi Puspita (Proceeding ICAMEKA: International Conference Accounting, Management & Economics Uniska, 2025)
Islamic Micro, Small, and Medium Enterprises (Islamic MSMEs) play a vital role in the regional economic structure as they contribute significantly to job creation, poverty reduction, and the strengthening of local economic resilience. This study aims to analyze the impact of Sharia-based financing on the performance and sustainability of Islamic MSMEs in East Java Province, focusing on the regions of Surabaya, Malang, and Jember. The research employs a quantitative approach using panel data from 2016 to 2023 and estimates the Fixed Effect Model (FEM). The results indicate that Sharia financing has a positive and significant effect on increasing the income and production capacity of Islamic MSMEs. Furthermore, interviews with MSME actors reveal that the values of justice, partnership, and blessing embedded in Sharia financing practices serve as non-material factors that strengthen long-term relationships between entrepreneurs and Islamic financial institutions. The policy implications highlight the importance of strengthening the Islamic MSME ecosystem through enhanced financial literacy, managerial training, and the digitalization of financial services to promote inclusive and equitable economic growth.